2020
DOI: 10.1186/s12944-020-01224-8
|View full text |Cite
|
Sign up to set email alerts
|

Could remnant-like particle cholesterol become a risk factor in diabetic menopausal women with coronary artery disease? A cross-sectional study of single academic center in China

Abstract: Background and aims: It has been confirmed that remnant-like particle cholesterol (RLP-C) mediates the progression of coronary artery disease (CAD). Currently there is limited information on RLP-C in menopausal women. With the special status of diabetes mellitus (DM) combined with the special body changes of the menopausal women, the RLP-C is particularly important when studying the changes that occurred in response to CAD and its associated risk factors. This study discussed whether RLP-C could be an independ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…High HDL levels have been well documented to exert a protective effect on CAD, and low plasma HDL elevated plasma TG levels are associated with an increased CAD risk. 23,24 Our results indicated that ε2 carriers had lower TC, LDL-C and TG levels than did ε3 or ε4 carriers among the control participants. However, no significant differences were found between ɛ2, ɛ3 or ɛ4 carriers and plasma lipoprotein levels among patients with CAD.…”
mentioning
confidence: 59%
“…High HDL levels have been well documented to exert a protective effect on CAD, and low plasma HDL elevated plasma TG levels are associated with an increased CAD risk. 23,24 Our results indicated that ε2 carriers had lower TC, LDL-C and TG levels than did ε3 or ε4 carriers among the control participants. However, no significant differences were found between ɛ2, ɛ3 or ɛ4 carriers and plasma lipoprotein levels among patients with CAD.…”
mentioning
confidence: 59%
“…Diabetic patients exhibit TG metabolism disorders and an atherogenic lipid profile in addition to carbohydrate metabolism disorder [ 1 ]. The dyslipidemia accompanying diabetes is characterized by high TG levels and low HDL-C levels [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have also revealed a link between reduced vitamin D and lipid profile, remnant cholesterol, and subsequent development of CVD [ 1 , 4 ]. Remnant cholesterol promotes atherosclerosis formation through several mechanisms, including upregulation of endothelial proinflammatory cytokines, monocyte migration and activation, and overproduction of prothrombotic factors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations